Experimental Investigation on the Behavior of Bracing Damper Systems by Utilizing Metallic Yielding and Recentering Material Devices - Jong Wan Hu; Myoung-hyun Noh; Jun-hyuck Ahn (Advances in Materials Science and Engineering)
With the aim of effectively reducing the structural damage caused by earthquake events, bracing systems equipped with retrofitting damper devices, which take advantage of the energy dissipation and impact absorption, have been widely used in practical construction sites. These bracing dampers, however, have been recognized as expendable supplies for easily replacing the damaged ones after a strong earthquake because they are commonly designed to undergo concentrated force and deformation for the purpose of protecting the main structural members such as the columns and beams. In this paper, the use of new superelastic shape memory alloy (SMA) dampers that can partially recover their original configuration is proposed to decrease the repair cost. In addition, the conventional steel dampers used for improving the energy dissipation arising due to metallic yielding are additionally integrated into the bracing member. The behaviors of such bracing systems with the damper devices were reproduced in experimental tests with the cyclic loading history, and then their strength capacity and recentering capability were estimated based on the experiment results. Finally, additional experimental tests were performed by imposing cyclic loading histories with different loading speeds on the superelastic SMA and steel plate damper specimens.